Hak Disabilitas dalam Pelayanan Surat Izin Mengemudi pada Satlantas Polres Purbalingga - Siva, Siva (Proceedings Series on Social Sciences & Humanities, 2024)
The right of persons with disabilities to obtain a driving license is a right that must be recognized and guaranteed to ensure accessibility and equality for everyone, including those with physical and mental limitations. In this regard, the government must ensure that the process of obtaining a driver's license is designed to be easily accessible and usable by everyone, including people with disabilities. In addition, the Government must provide special facilities and services that suit their needs, such as sign language interpreters or other tools to facilitate them.  In accordance with the provisions of article 28 h of the Law of the Republic of Indonesia which states that everyone has the right to obtain special facilities and services to achieve equality and justice. The government should also provide clear information on the procedures for obtaining a driver's license that covers all types of disabilities, such as guidance on the technical requirements and application process that apply to them. This will ensure that they have sufficient knowledge and feel supported when processing an extension or new driver's license. This research aims to examine how disability protection in obtaining a driver's license for persons with disabilities is a right of all citizens who meet the requirements. This case concerns National Police Chief Regulation No. 9/2012 on Driver's License. In this case, the case study was conducted at the Purbalingga Police Traffic Division Office. The method used in this research is a normative legal method with an empirical juridical approach, namely interviews and observations in the Purbalingga Regency area, then analyzed qualitatively to see whether it is in accordance with the National Police Chief Regulation Number 9 of 2012. Based on this. the findings obtained. And it is concluded that the implementation of Purbalingga Police in issuing driving licenses for persons with disabilities based on the National Police Chief Regulation is quite good, although overall it is not good enough. However, the technical implementation in the field has not been able to adapt to the situation of persons with disabilities.